Effect of Rebozo Tehnique Combined with Lavender Aromatherapy on the Duration of the Second Stage of Labor: A Quasi Experimental Study - Dyah Puji Astuti; Sumarni Sumarni; Fitria Prabandari; Diah Astutingrum; Levi Anatolia (An Idea Health Journal, 2026)
Introduction Prolonged labor is a childbirth complication that contributes to high maternal mortality and can negatively affect both the mother and the baby. Non-pharmacological interventions, such as the Rebozo technique and lavender aromatherapy, have proven to be effective in accelerating labor. However, studies that examine the effectiveness of both interventions remain limited. This study aimed to identify participant characteristics (age, parity, contractions, hemoglobin levels), assess intervention outcomes, measure the second stage duration after intervention, and analyze the relationship between the combination of Rebozo technique and lavender aromatherapy and the duration of the second stage of labor Methods This study used a quasi-experimental posttest-only design. Participants consisted of 32 laboring mothers selected through purposive sampling. Data were collected using observation sheets and analyzed using the Chi-square test. Results The results revealed that most participants were of ideal age (75%), multiparous (65.6%), had normal hemoglobin levels (78.1%), and experienced adequate uterine contractions (93.8%). A total of 65.6% of participants received the intervention completely, and after the intervention, 93.8% experienced a shorter second stage of labor than the theoretical duration. The Chi-square test indicated a significant relationship between the intervention and the duration of the second stage of labor (p = 0.044; X² = 4.073; OR = 1.222). Conclusions In conclusion, there is a significant relationship between the combined intervention of the Rebozo technique and lavender aromatherapy and the duration of the second stage of labor. Mothers who received the incomplete intervention had a 1.2 times higher risk of experiencing a prolonged second stage of labor compared wi